Modelling And Simulation Of The Driving Licence Application Queue Using Promodel Software At The Karawang Police Headquarters - Amelia Nur Fariza; Nizar Maulana Ibrahim (JTI: Jurnal Teknik Industri, 2025)
This study models and simulates the queue system for C driver's licence applications at the Karawang Police Station using ProModel to identify bottlenecks and evaluate improvement scenarios. As a baseline, the total actual time for applicants averaged 129.69 minutes, exceeding the standard of 120 minutes, with a daily output of 54 applicants (6 hours of operation). Two scenarios were proposed: (S1) adding registration units; (S2) adding 3 information units. The simulation results showed that S2 was the most effective: throughput increased from 54 to 139 applicants/day (+85), the aggregate ‘%full process’ percentage decreased from 15.49% to 2.12% (−13.37 points), and the average total waiting time decreased from 79.44 minutes to 68.8 minutes (-13.3%). The mean difference test (t-test, 95% CI) confirmed a significant improvement in waiting time and output. In practical terms, these results recommend a reorganisation of capacity at the clarification stage and arrival scheduling to reduce queues, thereby increasing citizen satisfaction and resource efficiency. Keywords: Bottleneck; Discrete Event Simulation; ProModel; SIM C; Queueing